Seeds of Change: exploring the transformative effects of seed priming in sustainable agriculture - Cañizares, Eva; Giovannini, Luca; Gumus, Berivan Ozlem; Fotopoulos, Vasileios; Balestrini, Raffaella; González Guzmán, Miguel; Arbona, Vicent (My University, 2025)
The threats posed by climate change on agriculture at a global scale have fostered researchers to explore new and efficient strategies to ensure stable and safe food production. These new strategies must not only be efficient in reducing yield loss but also comply with environmental and consumer safety regulations, which particularly refer to restrictions to pesticide application as well as the implementation of genetically modified organisms, including CRISPR/Cas edited lines. Among other approaches, priming constitutes an easier and relatively cheaper strategy to cope with the effects of abiotic and biotic stresses by boosting plants' endogenous potential. Particularly, pre-sowing seed priming has proven effective in improving germination and seedling establishment as well as tolerance to environmental and biotic factors throughout the plant's life cycle, exhibiting clear long-lasting effects. This tolerance response to a wide range of adverse factors is associated with physiological, metabolic and genetic mechanisms and responses at the seed level and subsequently in the established plant. The genetic and epigenetic mechanisms enabling this tolerance response in plants and their subsequent generation, as a transgenerational effect, will be reviewed. Finally, the potential of the different seed priming approaches contributing to an ecologically and economically more sustainable agriculture will be discussed.